2009
DOI: 10.1080/15504260903359015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Two Service Delivery Models for Homeless Individuals With Complex Behavioral Health Needs: Preliminary Data From Two SAMHSA Treatment for Homeless Studies

Abstract: Assertive Community Treatment (ACT) and the Comprehensive, Continuous, Integrated System of Care (CCISC) are two models for delivering services to homeless persons with complex behavioral health needs. This quasi-experimental study presents preliminary data comparing these two programs. The first program was based out of a community mental health center and utilized the ACT model of care with supported housing (ACT-SH), and the second program was based out of a substance abuse treatment agency and used the CCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 28 publications
1
32
0
4
Order By: Relevance
“…: unpublished data, 2020) identified 14 trials on permanent supportive housing (PSH). [30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several trials across Canada and the United States showed that PSH initiatives house participants more rapidly compared with usual services (73 v. 220 d; adjusted absolute difference 146.4, 95% confidence interval [CI] 118.0 to 174.9); 30 increase the number of people who maintain stable housing at 2 years (pooled odds ratio [OR] 3.58, 95% CI 2.36 to 5.43); 30,40 and significantly increase the percentage of days spent stably housed. 41 No trials showed a sig nificant improvement in mental health symptoms compared with standard care.…”
Section: Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…: unpublished data, 2020) identified 14 trials on permanent supportive housing (PSH). [30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several trials across Canada and the United States showed that PSH initiatives house participants more rapidly compared with usual services (73 v. 220 d; adjusted absolute difference 146.4, 95% confidence interval [CI] 118.0 to 174.9); 30 increase the number of people who maintain stable housing at 2 years (pooled odds ratio [OR] 3.58, 95% CI 2.36 to 5.43); 30,40 and significantly increase the percentage of days spent stably housed. 41 No trials showed a sig nificant improvement in mental health symptoms compared with standard care.…”
Section: Evidence Summarymentioning
confidence: 99%
“…44 No trials showed a significant improvement in substance use compared with standard care. 30,33,[41][42][43] Most trials reported no effect of PSH on acute care outcomes (e.g., number of emergency department visits and percentage of participants admitted to hospital). 30,41 However, 2 trials suggest that PSH participants had lower rates of hospital admission (rate reductions of 29%, 95% CI 10 to 44) and time in hospital (e.g., mean difference -31, 95% CI -48 to -14).…”
Section: Evidence Summarymentioning
confidence: 99%
“…Ein aktuelles Review bestätigt diese Effekte (40). Auch bei Wohnungslosen mit psychischen Störungen und komorbider Suchterkrankung verbessert ACT die psychische Gesundheit (58,72,73) oder lindert psychiatrische Symptomatik (39). Auch CTI erweist sich hier als wirksam, während für herkömmliches CM oder ICM kein entsprechender Effekt vorliegt (40).…”
Section: Psychische Gesundheit Und Substanzmittelmissbrauchunclassified
“…So finden sich für ACT keine signifikanten Einflüsse auf Konsummenge oder Missbrauchsschwere (40). Das trifft auch für Wohnungslose mit komplexem Bedarf oder Substanz-Komorbidität zu (72,73). Andere Studien finden mittels ACT in dieser Subgruppe eine deutliche Reduktion der Konsummenge (39,58).…”
Section: Psychische Gesundheit Und Substanzmittelmissbrauchunclassified
“…In the years since ACT was developed, it has been evaluated with a wide range of consumers including homeless persons (Coldwell & Bender, 2007;Lehman et al, 1999;Lehman, Dixon, Kernan, Deforge, & Postrado, 1997;Meisler, Blankertz, Santos, & McKay, 1997), mentally ill persons involved in the criminal justice system (Cosden, Ellens, Schnell, & Yamini-Diouf, 2005;Cosden, Ellens, Schnell, Yamini-Diouf, & Wolfe, 2003;McCoy, Roberts, Hanrahan, Clay, & Luchins, 2004;Meisler et al, 1997), and persons with co-occurring mental illness and substance use disorders Meisler et al, 1997). Additionally, studies have been conducted to determine ACT's impact on housing stability (Drake, Yovetich, Bebout, Harris, & McHugo, 1997;Lehman et al, 1997;Meisler et al, 1997), homeless persons with co-occurring mental health and substance use disorders (Young, Clark, Moore, & Barrett, 2009), mental illness symptom reduction (Coldwell & Bender, 2007;Cosden et al, 2005;Lehman et al, 1997), cost-effectiveness compared to traditional models (Essock, Frisman, & Kontos, 1998;Lehman et al, 1999), and drug and alcohol use (Cosden et al, 2005;Drake et al, 1998aDrake et al, ,1998b. Across populations and variables, ACT has consistently performed as well as other models of care, and in many instances it has outperformed other approaches on one or more of the outcomes discussed above.…”
mentioning
confidence: 99%